Teacher shortages, teacher contracts and their impact on education in Africa - Jean Bourdon; Katharina Michaelowa; Markus Frölich (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
Primary school enrolment rates are very low in francophone Africa. In order to enhance education supply, many countries have launched large teacher recruitment programmes in recent years, whereby teachers are no longer engaged on civil servant positions, but on the basis of (fixed-term) contracts typically implying considerably lower salaries and a sharply reduced duration of professional training. While this policy has led to a boost of primary enrolment, there is a concern about a loss in the quality of education. In this paper we analyse the impact on educational quality, by estimating nonparametrically the quantile treatment effects for Niger, Togo and Mali, based on very informative data, comparable across these countries. We find that contract teachers do relatively better for low ability children in low grades than for high ability children in higher grades. When positive treatment effects were found, they tended to be more positive at the low to medium quantiles; when negative effects were found they tended to be more pronounced at the high ability quantiles. Hence, overall it seems that contract teachers do a relatively better job for teaching students with learning difficulties than for teaching the more advanced children. This implies that contract teachers tend to reduce inequalities in student outcomes.
Keywords: 330